CULTURAL AND CREATIVE INDUSTRIES AS APPROACHES FOR REDUCING YOUTH UNEMPLOYMENT IN NIGERIA - Joshua, Omotosho Babatunde; Omotoso, Olukunle (Social Science Research, 2019)
It is no longer news that the nation is plagued with the challenge of unemployment and innocent youths are grossly affected with this menace. Several methods targeted at meeting this challenge have not yielded expected results. Data available on the number of unemployed youths is still worrisome. What becomes interesting is that among all the methods and strategies aimed at meeting this challenge, cultural industries have not attracted enough attention. The questions one needs to ask are: Why is this so? Are there no adequate industries (cultural and creative) in the country able to meet the employment needs of the youths? Is it not possible for the country to generate income from this economy if given enough attention as it obtains in other countries? What are the likely challenges that may hinder its development? All the issues and questions raised therefore become imperative considering the richness of culture in the country coupled with the high level of potentials inherent in Nigerian youths. This work therefore seeks to address the issues and questions raised with the aim of drawing the attention of stake holder to the need to harness this unique opportunity to meeting the challenges of unemployment in the country.